PENGARUH BESARAN ASET DAN OMSET BADAN USAHA MILIK DESA TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA WAY HAWANG KECAMATAN MAJE KABUPATEN KAUR - Alesia Maryanda Putri; Fachruzzaman Fachruzzaman (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the influence of the quantity of assets and turnover of Village-Owned Enterprises (BUMDes) on the welfare of the community in Way Hawang Village, Maje District, Kaur Regency. Methods: This study uses a quantitative approach by using primary data obtained directly from respondents through questionnaires. Sampling was carried out using the non-probability sampling method, the sample of this study amounted to 60 respondents who considered special criteria. The data analysis was conducted using multiple regression analysis with the SPSS version 30 program. Results: The results of the study show that the two independent variables, namely the amount of assets and the amount of turnover of BUMDes, have a positive and significant impact on the welfare of the community. The amount of assets has a dominant influence over turnover, with a stronger significance value. Keywords: Amount of Bumdes Assets, Amount of Bumdes Turnover, Community Welfare